Mobilität und Investitionsverhalten türkischer Gastarbeiter nach der Remigration - Toepfer, Helmuth (ERDKUNDE, 1980)
a) Urbanisation, as it is to be observed in Turkey, is greatly supported by the re-migration of former foreign workers (Fig. 1). b) Apart from regional mobility there is evidence of a strong sectoral mobility of re-migrants questioned, with the result that the proportion of those now employed in the tertiary sector has risen from 18.2 percent before emigration to 44.2 per cent after their return, and the proportion of those living from capital from 0 to 10 per cent (Fig. 1). c) The villages of the survey area profit but little from the investments of the re-migrants: while 17 per cent of the invested capital flowed into the villages, 54 per cent ended up in the two cities of the survey area, and the remaining 29 per cent even outside the area altogether (especially intoTrabzon, the provincial capital and to Instanbul) (Fig. 2). d) The greatest part of the investments serves to finance the building of houses and flats (42 per cent). Acquisition of land (building sites 17 per cent and agricultural usage 11 per cent) take second place. Tools, machines or participation in industrial enterprises on the other hand attract but little (9 per cent and 1 per cent of the investments). (Hg. 2). e) Due to the ever increasing difficulty of establishing a permanently secure existence at home the proportion of semi-permanent migrants (without fixed duration of stay) in Western Europe becomes larger, and with it grows the need for increased integration measures.